Constant Temperature Anemometer with Self-Calibration Closed Loop Circuit - Jamel Nebhen; Khaled Alnowaiser; Sofiene Mansouri (Applied Sciences, 2020)
In this paper, a Micro-Electro-Mechanical Systems (MEMS) calorimetric sensor with its measurement electronics is designed, fabricated, and tested. The idea is to apply a configurable voltage to the sensitive resistor and measure the current flowing through the heating resistor using a current mirror controlled by an analog feedback loop. In order to cancel the offset and errors of the amplifier, the constant temperature anemometer (CTA) circuit is periodically calibrated. This technique improves the accuracy of the measurement and allows high sensitivity and high bandwidth frequency. The CTA circuit is implemented in a CMOS FD-SOI 28 nm technology. The supply voltage is 1.2 V while the core area is 0.266 mm2. Experimental results demonstrate the feasibility of the MEMS calorimetric sensor for measuring airflow rate. The developed MEMS calorimetric sensor shows a maximum normalized sensitivity of 117 mV/(m/s)/mW with respect to the input heating power and a wide dynamic flow range of 0–26 m/s. The high sensitivity and wide dynamic range achieved by our MEMS flow sensor enable its deployment as a promising sensing node for direct wall shear stress measurement applications.